LEGAL LIABILITY OF THE PARTIES TO THE TRAGEDY OF THE MATCH AT KANJURUHAN STADIUM INDONESIA - Rianda Dirkareshza; M. Rizki Yudha Prawira (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2022)
Fanaticism towards high football in Indonesia has essentially been embedded in people's lives. The adverse impact of the phenomenon on his travels has evolved into hooliganism. The purpose of this article is to find out the responsibility of the parties to the tragedy of the match at the Kanjuruhan Stadium in Indonesia. The research methods used are Normative Juridical and Socio Phenomena to reveal cases that do not yet have permanent legal force (In Kracht) so that they are classified into a phenomenon, the approaches used are Statue Approach and the case approach. The results of the study revealed first, the organizing committee violated the provisions of Article 19 letter b of the FIFA Legal Handbook which states